Weak and classical solutions of equations of motion for third grade fluids - Bernard, Jean Marie (ESAIM: Mathematical Modelling and Numerical Analysis, 1999)
This paper shows that the decomposition method with special basis, introduced by Cioranescu and Ouazar, allows one to prove global existence in time of the weak solution for the third grade fluids, in three dimensions, with small data. Contrary to the special case where $\vertα_1+α_2\vert\le(24νβ)^{1/2}$, studied by Amrouche and Cioranescu, the H1 norm of the velocity is not bounded for all data. This fact, which led others to think, in contradiction to this paper, that the method of decomposition could not apply to the general case of third grade, complicates substantially the proof of the existence of the solution. We also prove further regularity results by a method similar to that of Cioranescu and Girault for second grade fluids. This extension to the third grade fluids is not straightforward, because of a transport equation which is much more complex. Dans cet article, on montre que la méthode de décomposition avec base spéciale introduite par Cioranescu et Ouazar, permet de démontrer l'existence globale en temps de la solution faible pour les fluides de grade trois, en dimension trois, avec des données petites. Contrairement au cas particulier où $\vertα_1+α_2\vert\le (24νβ)^{1/2}$, étudié par Amrouche et Cioranescu, la norme H1 de la vitesse n'est pas majorée pour toute donnée. Ce fait, qui conduisait à penser, en contradiction avec cet article, que la méthode de décomposition ne pouvait pas s'appliquer au cas général du grade trois, complique substantiellement la démonstration d'existence de la solution. On établit des résultats de régularité par une méthode similaire à celle de Cioranescu et Girault pour des fluides